Kinesiophobia determinants in patients after myocardial infarction - Kocjan, Janusz (Journal of Education, Health and Sport, 2017)
Introduction:In the most cases, the causes of morbidity in cardiovascular diseases is lack of regular physical activity. Kinesiophobia, defined as fear before movement may significantly contribute to the occurence and intensification of hypokinesis. Aim of the study: Determine the level of barriers of a physical activity (kinesiophobia) in patients after Myocardial Infarction (MI). Decided also examine that selected variables: age, BMI, elapsed time since MI and health self-assessment have impact to the general level of kinesiophobia (KCS) and domains: biological (BD) and psychological (PD). Materials and methods: 64 patients, in age of 47-84 years, after MI: 32 females (age: mean 64.0 ± 9.9 years; BMI: mean 27.1 ± 4,3; Time since MI: mean 10.6 ± 8.5 months) and 32 males (age: mean 67.1 ± 9.7 years; BMI: mean 27.1 ± 3.18; Time since MI: mean 8.7 ± 6.9 months) – patients undergoing cardiology treatment – were examined. Kinesiophobia Causes Scale (KCS), SF-36 ( Short Form Health Survey) and author metrics were used. Results: Patients presented elevated level of kinesiophobia, in general (females: x = 48.7 ± 15.1; males: x = 46.2 ± 10.6) as well as in biological domain (females: x = 42.6 ± 15.9; males: 40.5 ± 10.9) and psychological domains (females: 54.8 ± 16.3; mężczyźni: 51.8 ± 14.9). In women, BMI index correlated with: BD (r=0.541), PD (r=0.560) and KCS (r=0.566) and were also noted correlations between time since MI and: DB: r=0.408; PD: r=0.591 and KCS: r=0.524). Besides, health factor: physical functioning correlates with: BD: r= – 0,528; DP: r= -0.619 and KCS: r=-0.661. In men, only KCS correlated with pain factor r=-0.407. Conclusions: In females, BMI and time since MI strongly determine the level of kinesiophobia. In men, disposition seems to be constans. Higher intensification of kinesiophobia in psychological domain suggest take into account psychological sphere in cardiac rehabilitation process. Identification and early diagnosis of the causes of motor passivity is very important, both in primary and secondary prevention.